Studi Perbandingan Aktivitas Antioksidan Xantofil dan Karoten Kapang Oncm Merah pada Berbagai Waktu Inkubasi: Comparison Study of Antioxidant Activity of Xanthophyll and Carotene from Red Oncom Mold In Various Incubation Times - Sriwulan Indriani Pea; Khairuddin; Prismawiryanti (KOVALEN: Jurnal Riset Kimia, 2020)
Research on a comparative study of antioxidant activity of xanthophyll and carotenoids from red oncom, mold in various incubation times has been studied. This study aims to determine the antioxidant activity of xanthophyll and carotene at various incubation times of red oncom cultured in corn cob medium. This study used a Completely Randomized Design (CRD) at variations in incubation time: 2, 3, 4, 5, 6, and 7 days. The results showed that the best antioxidant activity of xanthophyll and carotene was on the second day with antioxidant activity of 82.27% and 65.80%, respectively. Keywords: antioxidant activity, xanthophyll, carotene, carotenoids, red oncom